DAMPAK PERUBAHAN STRATEGIK TERHADAP STRUKTUR DAN BUDAYA ORGANISASIONAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Turbulent environments are forcing organizations to launch revolutionary changes in their basic strategic capabilities, internal structures, and corporate cultures. ReengMeering, restructuring, rightsizing, and rethinking all represent attempts to implement such fundamental changes. This article emphasizes the need to create sustainable competitive advantage by developing three critical organizational capabilities - organizational learning, ability to create new knowledge, and strategy-culture matching. To develop these capabilities, organizations are forced to rethink how they design their structures and to recast their corporate culture. For the coming decade organizational design needs to be simpler, flatter, leaner, more flexible and lateral. Networks and teams are also importantfeatures of the future structural design. Moreover, this transition from "boss class" hierarchy to new design requires afundamental change in corporate cultures. To generate strategic change means reshaping a corporate culture whose dominant values are more consistent with the new strategic challenge. It is essential for corporate cultures to become thinner, less focused on conformity, and more capable of enhancing organizations' flexibility.